Sent from the Heavens, Received in Budapest - Bakos Áron (Hungarian Studies Yearbook)
The paper examines heavenly letters by combining folkloristic, historical, and anthropological perspectives. First, it analyses and compares variations collected by Hungarian folklorists, critically evaluating their findings. Secondly, to reframe these interpretations and explore the character and late modern uses of the letters, the paper traces the origins of this tradition, and looks at the early medieval counterparts of the letters. Based on this brief review of their original form and function, the paper offers an anthropological reading of the communicative role of the letters. My central argument is that through the mere act of copying the metonymic relationship between the letter and the divine power is metaphorically altered, and that the act of copying gradually became an expressive, rather than a technical action. As a result, the changes in their character, the various protective functions incorporated into them or associated with their possession, can be understood as part of a process in which heavenly letters shifted from being indexes to signals.